Hedgehog signaling enables nutrition-responsive inhibition of an alternative morph in a polyphenic beetle - Kijimoto, Teiya (Proc Natl Acad Sci U S A, 2016)
The recruitment of modular developmental genetic components into new developmental contexts has been proposed as a central mechanism enabling the origin of novel traits and trait functions without necessitating the origin of novel pathways. Here, we investigate the function of the hedgehog (Hh) signaling pathway, a highly conserved pathway best understood for its role in patterning anterior/posterior (A/P) polarity of diverse traits, in the developmental evolution of beetle horns, an evolutionary novelty, and horn polyphenisms, a highly derived form of environment-responsive trait induction. We show that interactions among pathway members are conserved during development of Onthophagus horned beetles and have retained the ability to regulate A/P polarity in traditional appendages, such as legs. At the same time, the Hh signaling pathway has acquired a novel and highly unusual role in the nutrition-dependent regulation of horn polyphenisms by actively suppressing horn formation in low-nutrition males. Down-regulation of Hh signaling lifts this inhibition and returns a highly derived sigmoid horn body size allometry to its presumed ancestral, linear state. Our results suggest that recruitment of the Hh signaling pathway may have been a key step in the evolution of trait thresholds, such as those involved in horn polyphenisms and the corresponding origin of alternative phenotypes and complex allometries.